Giving regenerative agriculture an agronomic perspective: a proposed framework from the food and beverage industry - Klauser, Dominik; de Candido, Julia; Clark, Alexa; Leclerc, Yves; Drabaek, Iver; Henry, Margaret; Lockwood, Sarah; Thomson, Rebecca; Lawrence, Joanna; Henry, Martina; Chapot, Pascal; Urbano, Lucas; et al. (Frontiers in Sustainable Food Systems, 2025)
Food systems face significant challenges that include increasing demand for agricultural products and accelerating environmental degradation. Regenerative agriculture has emerged as concept to reduce environmental harm while maintaining or even improving productivity. However, adoption of regenerative agriculture remains limited. This partly due to the absence of a shared definition and a standardised process to monitor, assess and report regenerative agriculture outcomes. To address this gap, SAI Platform, a member-led organisation within the food and beverage sector, collaborated with stakeholders to develop a global framework for regenerative agriculture. Drawing from a review of existing frameworks and consultations with SAI Platform members, farmers, and academics, we developed a framework that defines regenerative agriculture as an outcome-based approach that enhances environmental impact. It includes eight regenerative agriculture outcomes across the environmental areas of soil health, biodiversity, water and climate and suggests indicators to quantify progress. The framework process emphasises the need to understand local contexts and farmer needs when implementing regenerative agriculture. It does so through a four-step process that includes (i) a context analysis to identify key material criteria of a production system, (ii) the prioritisation of outcomes based on the context analysis, (iii) the selection of practices to achieve improved performance against prioritised outcomes, and (iv) the development and implementation of continuous improvement plans to monitor and report progress. Farm groups or individual farms can use this framework to independently verify the implementation of the steps defined in the framework and claim different performance levels for progress towards regenerative agriculture. These claims create a foundation for regenerative agriculture programmes, incentive mechanisms, and corporate reporting. While the framework is a starting point, collaboration and refinement are necessary to address evolving challenges in implementation. SAI Platform commits to research and stakeholder engagement to continuously improve the framework and support fair transitions towards regenerative agriculture.